Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/imb.12302
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of Laodelphax striatellus (Insecta: Hemiptera: Delphacidae) neutral sphingomyelinase

Abstract: The neutral sphingomyelinase (nSMase) 1 homologue gene LsSMase was cloned from Laodelphax striatellus, a direct sap-sucker and virus vector of gramineous plants, and expressed via a Bac to Bac baculovirus expression system. The LsSMase-enhanced green fluorescent protein fusion protein was located in the endoplasmic reticulum in a similar manner to mammalian nSMase 1. The biochemical properties of LsSMase were determined in detail. The optimal pH and temperature for recombinant LsSMase were 8 and 37 °C, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Indeed, treating FhEVs with GW4869 inhibited FhEVassociated neutral SMase activity in a dose-dependent manner. However, residual activity following GW4869 treatment suggests that FhSMPD2 may be refractory to this inhibitor (compared to human enzymes) as has been reported for insect SMase (Zhou et al 2017).…”
Section: Discussionmentioning
confidence: 84%
“…Indeed, treating FhEVs with GW4869 inhibited FhEVassociated neutral SMase activity in a dose-dependent manner. However, residual activity following GW4869 treatment suggests that FhSMPD2 may be refractory to this inhibitor (compared to human enzymes) as has been reported for insect SMase (Zhou et al 2017).…”
Section: Discussionmentioning
confidence: 84%
“…The sphingomyelinase (SMPD) of Bombus lantschouensis , which was highly expressed in the ovary and pupa of the queen bee, mediated the pupa development (Han et al, 2017; Han et al, 2018). One neutral SMase ( LsSMase ) was reported in Laodelphax striatellus and showed the highest expression in the ovary in female adults (Zhou et al, 2017). Moreover, it had been reported that the disruption of sphingolipid metabolism elicited reproductive defects in Drosophila (Guo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%